Answer:
(1/6)(-10x - 4) = -4
Step-by-step explanation:
(1/6)(-3x - 24) = -4
=> -3x - 24 = -4 x 6
=> -3x - 24 = -24
=> -3x = 24 - 24
=> -3x = 0
=> x = 0 (not 2) => Incorrect option
(1/6)(-5x - 8) = -4
=> -5x - 8 = -4 x 6
=> -5x - 8 = -24
=> -5x = 8 - 24
=> -5x = -16
=> x = 16/5 (not 2) => Incorrect option
(1/6)(-10x - 4) = -4
=> -10x - 4 = -4 x 6
=> -10x - 4 = -24
=> -10x = 4 - 24
=> -10x = -20
=> x = 2 => Correct option
(1/6)(-12x - 16) = -4
=> -12x - 16 = -4 x 6
=> -12x - 16 = -24
=> -12x = 16 - 24
=> -12x = 8
=> x = -3/4 (not 2) => Incorrect option
=> Option C is correct
Hope this helps!